The Myth of community : gender issues in participatory development - Guijt, Irene; Shah, Meera Kaul. (New Delhi : Vistaar Publications, 1999)
Papers presented at a two-day workshop at Institute of Development Studies at University of Sussex, U.K. in December 1993.
Includes bibliographical references and index.
Keywords: sociology; Women -- Developing countries -- Social conditions